In vivo comparison of synthetic macroporous filamentous and sponge-like skin substitute matrices reveals morphometric features of the foreign body reaction according to 3D biomaterial designs - Barsch, Friedrich; Mamilos, Andreas; Schmitt, Volker H.; Babel, Maximilian; Winter, Lina; Wagner, Willi Linus; Winther, Hinrich; Ottomann, Christian; Niedermair, Tanja; Schreml, Stephan; Hierlemann, Helmut; Brochhausen, Christoph (Cells, 2022)
Synthetic macroporous biomaterials are widely used in the field of skin tissue engineering to mimic membrane functions of the native dermis. Biomaterial designs can be subclassified with respect to their shape in fibrous designs, namely fibers, meshes or fleeces, respectively, and porous designs, such as sponges and foams. However, synthetic matrices often have limitations regarding unfavorable foreign body responses (FBRs). Severe FBRs can result in unfavorable disintegration and rejection of an implant, whereas mild FBRs can lead to an acceptable integration of a biomaterial. In this context, comparative in vivo studies of different three-dimensional (3D) matrix designs are rare. Especially, the differences regarding FBRs between synthetically derived filamentous fleeces and sponge-like constructs are unknown. In the present study, the FBRs on two 3D matrix designs were explored after 25 days of subcutaneous implantation in a porcine model. Cellular reactions were quantified histopathologically to investigate in which way the FBR is influenced by the biomaterial architecture. Our results show that FBR metrics (polymorph-nucleated cells and fibrotic reactions) were significantly affected according to the matrix designs. Our findings contribute to a better understanding of the 3D matrix tissue interactions and can be useful for future developments of synthetically derived skin substitute biomaterials.
Gesehen am 02.11.2022